Освітня траєкторія ЄС у впровадженні штучного інтелекту (MCIT: Proceedings of International scientific and practical conference, 2025)
Проведено дослідження передумов застосування ШІ у сфері ЄС. Здійснено аналіз основних можливостей та напрямів застосування ШІ. Розкрито правове й політичне регулювання ШІ в ЄС. Виокремлено виклики та ризики використання ШІ у сфері освіти. Висунуто рекомендації та перспективи щодо використання ШІ у сфері освіти.A study of the prerequisites for the application of AI in the EU was conducted. An analysis of the main opportunities and directions for the application of AI was carried out. The legal and political regulation of AI in the EU was revealed. The challenges and risks of using AI in education were identified. Recommendations and prospects for the use of AI in education were put forward.